Pengaruh Pembelajaran Aqidah Akhlak Berbasis Problem Based Learning untuk Meningkatkan Hasil Belajar Siswa Kelas VIII di SMPN 1 Sukorame - Anggraeni Dwi Cahyani; Amrini Shofiyani (ANWARUL, 2026)
Aqidah Akhlak learning at SMPN 1 Sukorame is still dominated by conventional teacher-centered methods through one-way lectures, resulting in low student activeness, intellectual engagement, and learning outcomes. This study aimed to determine the influence and effectiveness of implementing the Problem Based Learning (PBL) model on the Aqidah Akhlak learning outcomes of Grade VIII F students at SMPN 1 Sukorame. This study used a quasi-experimental method with a One-Group Pretest–Posttest design, involving 30 Grade VIII F students as research subjects. Data were collected through pretest and posttest tests as well as student response questionnaires, then analyzed using the normality test, N-Gain Score test, and Paired Samples T-Test with the assistance of SPSS. The results showed a significant improvement in learning outcomes after the implementation of the PBL model. The Paired Samples T-Test obtained a significance value of 0.000 < 0.05, so H₀ was rejected and the PBL model was declared to have a significant effect on students’ learning outcomes. The N-Gain Score of 0.389 was in the moderate category, indicating that the PBL model was effective in improving Aqidah Akhlak learning outcomes. These findings affirm that authentic problem-based learning can serve as a pedagogical alternative to promote active participation, critical thinking skills, collaboration, and a more meaningful understanding of Islamic values.